(untitled) (International Journal of Environmental Sciences, 2025)
Purpose: Bone tissue engineering (BTE) faces significant challenges in replicating the natural bone environment and ensuring long-term viability of engineered tissues. This study investigated the potential of biphasic calcium phosphate (BCP) scaffolds integrated with collagen (Col), chitosan (Ch), and hyaluronic acid (HyA) to enhance bone regeneration. Methods: BCP scaffolds were prepared using the sponge replica method and functionalized with Col, Ch, and HyA to mimic the extracellular matrix. Fourier transform infrared (FTIR) spectroscopy was used to confirm the incorporation of biomaterials. Scanning electron microscopy (SEM) was employed to examine the scaffold morphology. In vitro bioactivity assays were performed using simulated body fluids. MTT assays using MRC-5 cells were performed to assess cytocompatibility. Swelling and degradation studies were performed to evaluate hydrophilicity and biodegradability. Results: FTIR confirmed the successful incorporation of Col, Ch, and HyA into the BCP scaffolds. SEM revealed a highly porous, interconnected structure with rough surfaces. In vitro bioactivity assays showed bone-like apatite formation after 14 days. MTT assays demonstrated enhanced cytocompatibility of Col-Ch-HyA-BCP scaffolds compared to that of plain BCP scaffolds. The composite scaffolds exhibited higher water uptake and faster degradation rates than BCP, indicating improved hydrophilicity and biodegradability. Conclusion: BCP scaffolds functionalized with Col, Ch, and HyA provide a promising platform for bone tissue engineering, offering a conducive microenvironment for cell attachment, proliferation, and differentiation. Further in vivo studies are required to validate the efficacy of these scaffolds in promoting bone regeneration.